Major congenital anomalies in babies born with Down syndrome: A EUROCAT population‐based registry study. Issue 12 (24th September 2014) - Morris, Joan K.; Garne, Ester; Wellesley, Diana; Addor, Marie‐Claude; Arriola, Larraitz; Barisic, Ingeborg; Beres, Judit; Bianchi, Fabrizio; Budd, Judith; Dias, Carlos Matias; Gatt, Miriam; Klungsoyr, Kari; et al.
<x xml:space="preserve">Abstract</x> Previous studies have shown that over 40% of babies with Down syndrome have a major cardiac anomaly and are more likely to have other major congenital anomalies. Since 2000, many countries in Europe have introduced national antenatal screening programs for Down syndrome. This study aimed to determine if the introduction of these screening programs and the subsequent termination of prenatally detected pregnancies were associated with any decline in the prevalence of additional anomalies in babies born with Down syndrome. The study sample consisted of 7, 044 live births and fetal deaths with Down syndrome registered in 28 European population‐based congenital anomaly registries covering seven million births during 2000–2010. Overall, 43.6% (95% CI: 42.4–44.7%) of births with Down syndrome had a cardiac anomaly and 15.0% (14.2–15.8%) had a non‐cardiac anomaly. Female babies with Down syndrome were significantly more likely to have a cardiac anomaly compared to male babies (47.6% compared with 40.4%, P < 0.001) and significantly less likely to have a non‐cardiac anomaly (12.9% compared with 16.7%, P < 0.001). The prevalence of cardiac and non‐cardiac congenital anomalies in babies with Down syndrome has remained constant, suggesting that population screening for Down syndrome and subsequent terminations has not influenced the prevalence of specific congenital anomalies in these babies. © 2014 Wiley Periodicals, Inc.